2019
DOI: 10.1021/acsomega.9b01274
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Tissue Transglutaminase for Self-Catalytic Cross-Linking of Self-Assembled Collagen Fibril Hydrogel and Its Promising Application in Wound Healing Promotion

Abstract: Collagen-based bio-hydrogels are undoubtedly a hot spot in the development of biological dressings for wound healing promotion. Herein, glutamine transaminase (TGase), a biological nontoxic cross-linker with high specific activity and reaction rate under mild conditions, was utilized for the self-catalytic cross-linking of the regenerated collagen (COL) fibril hydrogel fabricated through a molecular self-assembly method. The results showed that the natural triple helical conformation of COL remained completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 47 publications
1
28
0
1
Order By: Relevance
“…[62] "Biological" nontoxic crosslinker, TG, has advantages over chemical crosslinkers as it shows greater specificity, milder reaction condition, and higher biodegradability. [63][64][65] As discussed in the previous section, TG is involved in in vivo crosslinking processes to assist collagen assembly. Reconstituted TG-crosslinked collagen did not increase the denaturation temperature despite showing stabilization of triple helix.…”
Section: Exogenous Collagen Crosslinkingmentioning
confidence: 99%
“…[62] "Biological" nontoxic crosslinker, TG, has advantages over chemical crosslinkers as it shows greater specificity, milder reaction condition, and higher biodegradability. [63][64][65] As discussed in the previous section, TG is involved in in vivo crosslinking processes to assist collagen assembly. Reconstituted TG-crosslinked collagen did not increase the denaturation temperature despite showing stabilization of triple helix.…”
Section: Exogenous Collagen Crosslinkingmentioning
confidence: 99%
“…Tremella polysaccharide can be used as a natural moisturizer to relieve skin dehydration, repair the skin barrier and maintain skin health. 74 The desorption kinetic simulation method was used to study the moisture content stability and characteristics of Tremella polysaccharides obtained under different drying conditions, and the results showed that the Tremella polysaccharides obtained by each drying method had good moisturising and hygroscopic ability. 75 Tremella polysaccharides can reduce the photo-damage of skin caused by ultraviolet rays.…”
Section: Skin Protectionmentioning
confidence: 99%
“…Tremella polysaccharide can be used as a natural moisturizer to relieve skin dehydration, repair the skin barrier and maintain skin health. 74 …”
Section: Biological Activity Mechanism Of Tremella Polysaccharidementioning
confidence: 99%
“…Jiang et al developed collagen-fibril hydrogel crosslinked by transglutaminase for skin regeneration. 55 When 40 U/g of transglutaminase was treated to collagen, transglutaminase efficiently made collagen self-assembled. Jiang et al demonstrated that the thermostability of collagen fibrils could be increased by adjusting the transglutaminase concentration, varying the thermal denaturation temperature from 60.6 (collagen only) to 82.8 °C (with 80 U/g of transglutaminase).…”
Section: Recent Applications Of Enzyme-mediated Crosslinkable Hydrogementioning
confidence: 99%